In Search of a Model for the Legal Protection of a Whistleblower in the Workplace in Poland. A legal and comparative study. - Bolesta, Łukasz (Peter Lang International Academic Publishers, 2020)
The legal situation of whistleblowers has become an object of keen public interest in recent years. As practice shows, people who reveal irregularities in the workplace are exposed to the negative consequences of their actions. This book proposes a model of legal protection of such people, which could be applied in the Polish legal order. This model has been designed on the basis of an analysis of the literature, jurisprudence and selected legal acts existing in the world in the field of whistleblowers' protection.
Keywords: Comparative law.; Whistle blowing -- Law and legislation -- Poland.; Bolesta; comparative; Context; Duty of loyalty; Employee; Employer; Legal; Model; Poland; Polish; Protection; Reporting; Search; study; Transparency; Whistleblower; Whistleblowing; Workplace